Incidence and Risk Factors of Dry Eye in Children and Adolescents With Diabetes Mellitus: A 3-Year Follow-Up Study - Zhangling Chen (Frontiers Media S.A., 2021)
Purpose: To investigate the incidence and risk factors of dry eye in children with diabetes mellitus (DM) over a period of 3 years.Methods: Children and adolescents with DM (age: 3–14 years) from the Shanghai Children and Adolescent Diabetes Eye (SCADE) study cohort who did not have dry eye in January 2018 were followed-up for 3 years and re-examined in January 2021, and the incidence rate and risk factors for dry eye were calculated.Results: Forty children and adolescents with DM came for follow-up in 2021. Nine of them were diagnosed with dry eye, resulting in a 3-year incidence rate of 22.5% and an annual mean incidence rate of 7.5% for dry eye. Univariate regression analysis confirmed that decreased corneal sensation (OR [Odds Ratio] = 25.60; 95%CI [Confidence Interval] = 1.31~501.69; P = 0.03) was the risk factor for dry eye incidence. Long course of DM (OR = 1.80; 95%CI = 0.96~3.38; P = 0.07), eye pain (OR = 12.27; 95%CI = 0.65~231.48; P = 0.09), and dry eye in parents (OR = 15.99; 95%CI = 0.76~337.75; P = 0.08) may interfere with the incidence of dry eye in them.Conclusions: The incidence of dry eye in children and adolescents with DM is high.